2009
DOI: 10.1161/hypertensionaha.109.135046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Mercury Exposure and Blood Pressure Among Nunavik Inuit Adults

Abstract: Abstract-Epidemiological evidence suggests a negative impact of methylmercury on the cardiovascular system, but findings regarding the effect on blood pressure (BP) are not consistent. We aimed to study the impact of mercury levels on BP among Nunavik Inuit adults. The health survey Qanuippitaa? was conducted in Nunavik (northern Quebec, Canada), and data were obtained from 732 Inuit Ն18 years of age. Anthropometric blood samples, as well as systolic BP and diastolic BP, were assessed. Pulse pressure (systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 38 publications
1
94
4
Order By: Relevance
“…The prevalence of diabetes in Nunavik is low (3.5%) and no association has been observed between Se status and diabetes or plasma fasting glucose and insulin levels (Chateau-Degat et al, 2010). An inverse association between blood Se and systolic blood pressure has also been reported (Valera et al, 2009). Hansen et al (2004) pointed out that there are no recorded signs of selenosis in Greenland populations despite their high Se intake and suggest that these populations may tolerate higher Se concentrations.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The prevalence of diabetes in Nunavik is low (3.5%) and no association has been observed between Se status and diabetes or plasma fasting glucose and insulin levels (Chateau-Degat et al, 2010). An inverse association between blood Se and systolic blood pressure has also been reported (Valera et al, 2009). Hansen et al (2004) pointed out that there are no recorded signs of selenosis in Greenland populations despite their high Se intake and suggest that these populations may tolerate higher Se concentrations.…”
Section: Discussionmentioning
confidence: 72%
“…Lower Se toxicity from naturally high-Se diet has also been observed in Inuit populations, whose traditional diet of marine mammals is exceptionally rich in Se. In Greenland and Nunavik, B-Se status varies between 80 and 3550 μg/L (Hansen et al, 2004;Valera et al, 2009). The prevalence of diabetes in Nunavik is low (3.5%) and no association has been observed between Se status and diabetes or plasma fasting glucose and insulin levels (Chateau-Degat et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that higher hair mercury content is associated with increased risk of CVD in men in this study population. 19,31 Other studies have found a positive association between mercury exposure and blood pressure not only in populations with high mercury exposure, [20][21][22][23] but also among non-fish consumers. 37 However, our Long-chain n-3 PUFA, mercury and blood pressure JK Virtanen et al results indicate that a moderate mercury exposure is not associated with blood pressure, and also the overall evidence regarding the association between mercury exposure and blood pressure is considered weak.…”
Section: Discussionmentioning
confidence: 98%
“…19 Mercury has also been associated with blood pressure in other, but mainly highly exposed study populations. [20][21][22][23] However, little is known about the relationship in populations with low to moderate exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…1 Epidemiological evidence suggests a negative impact of methylmercury on the cardiovascular system, but the effects on BP are inconsistent. 7,8 A recent survey of Inuit from Nunavik, who are highly exposed to environmental methylmercury, showed that circulating methylmercury levels were associated with increasing systolic BP and pulse pressure after controlling for the confounding factors. 7 Intriguingly, when this association was adjusted by n-3 PUFA and selenium, the association between methylmercury and BP became more prominent.…”
mentioning
confidence: 99%